Validity and Reliability of Needs Analysis Questionnaire for Dyscalculia Instrument - Yoong, Soo May; Hosshan, Hasrul; Arumugam, Shyielathy; Alya Qasdina Ng Ai Lee; Lau, Shiau Ching; Govindasamy , Parthiban (South Asian Journal of Social Sciences and Humanities, 2022)
Dyscalculia is a specific learning difficulty in Mathematics. Intervention instrument is needed to assist the pupils to overcome their learning difficulties during this situation. Thus, this paper presents the evaluation of validity and reliability of a needs analysis questionnaire to investigate the needs to design and develop a dyscalculia instrument. This four-point Likert-type scale questionnaire consisted of 46 items that represented four constructs. The assessment of content validity is done through nine domain experts. Content validity index and Kappa statistics were implemented for content validity. After the validity analysis, one construct with low scale content validity index (S-CVI) and another three items with low item content validity index (I-CVI) and Kappa statistics had been removed. Overall, a number of 13 items had been removed and 33 items had been retained. Subsequently, reliability analysis was done by carrying out a pilot test. During the pilot test, the questionnaire had been implemented among 30 Mathematics teachers to obtain the Cronbach’s Alpha value. One item had been removed after the reliability analysis due to the low value of [corrected item-total correlation] and 32 items were retained. Thereafter, the questionnaire was ready to be used for data collection in the actual study. As stated in the preceding statement, it will assist teachers in identifying problems and planning appropriate interventions to meet the needs of dyscalculic students.